Pengaruh Kompensasi dan Lingkungan Kerja terhadap Kinerja melalui Loyalitas Karyawan: Studi pada Industri Tenun P40 Ngawi - Silfi Aulia Rahmadani; Ely Masykuroh (Niqosiya: Journal of Economics and Business Research, 2025)
This research is driven by the low employee performance at P40 Kedunggalar Weaving Industry, as evidenced by production results that have yet to meet standards and a low level of work discipline. The compensation provided has not optimally motivated employees, although employee loyalty is relatively high. The physical work environment is fairly good, but a professional work culture has not been fully established. Using a quantitative approach through path analysis methods, the population in this study consists of all P40 Weaving employees, totaling 50 people. The results of the study indicate that compensation and the work environment have a positive and significant effect on employee performance. Compensation and the work environment also have a significant effect on employee loyalty, which ultimately impacts performance improvement. Loyalty has been proven to mediate the influence of compensation and the work environment on employee performance.